Implementasi Layanan Bimbingan Rohani Pasien di Rumah Sakit Umum Siaga Medika Purbalingga - Nur Isnaeni Barokah; Mafaaza Alhaqqi (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Self-confidence is a crucial element in preparing preoperative patients as it can influence the outcomes of surgical procedures and postoperative recovery. Prayer therapy is one alternative approach that has been employed in the context of complementary and integrative medicine to enhance individuals' psychological well-being. This review aims to evaluate the effectiveness of prayer therapy in enhancing self-confidence among preoperative patients. This study was conducted through a literature review of relevant scientific articles on prayer therapy, self-confidence, and preoperative preparation. Literature searches were performed on reputable academic databases using relevant keywords. The inclusion criteria were studies investigating the influence of prayer therapy on self-confidence among preoperative patients. The results of this literature review indicate that prayer therapy can be effective in enhancing self-confidence among preoperative patients. Prayer, as a form of worship in Islam, involves physical movements, relaxation, focused concentration, and spirituality. This activity can help reduce anxiety, improve focus, and provide emotional stability to patients. Through regular engagement in prayer, patients can develop a sense of self-confidence, enhance their belief in their ability to face the surgical procedure and acquire the mental strength necessary to overcome the physical and emotional challenges associated with surgery. Penelitian ini dilakukan bertujuan untuk mendapat pengetahuan mengenai Penerapan layanan bimbingan rohani pasien di Rumah Sakit Siaga Medika Purbalingga. Hal ini tentunya akan sangat penting untuk membantu kesembuhan pasien, di mana pasien membutuhkan layanan pengobatan secara fisik dan non fisik. Layanan rohani di rumah sakit sangatlah diperlukan demi mewujudkan pengobatan holistik sehingga pasien dan keluarga pasien dapat tetap dekat dengan Tuhan. Jenis penelitian ini ialah penelitian kualitatif. Sedangkan metode yang digunakan dalam penelitian adalah metode fenomenologi. dengan teknik pengumpulan data yang digunakan ialah observasi dan wawancara dengan mewawancarai 3 narasumber yang berprofesi sebagai rohaniawan di rumah sakit di Rumah Sakit Siaga Medika Purbalingga. Hasil penelitian bahwa layanan bimbingan rohani di rumah sakit di Rumah Sakit Siaga Medika Purbalingga didukung oleh jumlah rohaniawan yang tersedia, sasaran pasien yang mendapatkan bimbingan rohani, metode penyampaian bimbingan rohani, kedalaman dan keluasan materi yang diberikan oleh rohaniawan kepada pasien dan keluarganya, kuantitas bimbingan rohani, mekanisme informasi bimbingan rohani, hingga evaluasi layanan bimbingan rohani yang terdapat didalamnya. Bimbingan rohani Islam di Rumah Sakit Siaga Medika Purbalingga diberikan untuk memberikan bimbingan layanan ibadah selama mendapatkan perwatan serta untuk memberikan motivasi sembuh bagi pasien.